Trends and factors associated with dairy calf early slaughter in Ireland, 2018–2022 - Byrne, Andrew W.; Ronan, Stephanie; Doyle, Rob; Blake, Martin; Ryan, Eoin (Frontiers in Veterinary Science, 2023)
Dairy systems require that each cow calves annually to have an efficient milk production cycle. In systems where milk production is maximised, the male offspring from dairy breed sires tend to have poor beef production traits and, therefore, can be of low economic value. Few studies have been published on the factors impacting early slaughtering of calves in peer-reviewed literature. Here we present an analysis of national data on calves slaughtered from 2018-2022 in Ireland. Data (Jan 2018-May 2022) on all cattle <6 months of age were collated at a national level and were described at calf-, herd-, and county-levels. These data were statistically analysed at per-capita slaughter rates (calves/calf born) using negative binomial regression models with an offset. There were 125,260 calves slaughtered early (1.09% of total births) recorded in the dataset from 1,364 birth herds during the study period, of which 94.8% (118,761) were male. 51.7% were classified as Friesian-cross (FRX), 11.5% Friesian (FR) and 32.1% Jersey-cross (JEX). The median age at slaughter was 16 days (Mean:18.9 days; IQR:13-22). The median calves/herd slaughtered was 16 (mean:91.8); median calves/herd/year slaughtered was 21 (mean:42.0). There was substantial variation in counts of calves slaughtered across herds, years, and counties. Herd calf slaughter rates and per capita calf slaughter rates increased significantly in 2022, with the highest rates over the time series. Calf slaughter rates varied significantly with herd size, year, and major breed (Jersey; JE). Herds which were more recently established tended to have higher calf slaughter rates. Herds that repeatedly slaughtered calves over 2 or more years tended to be larger and slaughtered more calves/herd/year. The slaughtering of calves is not widespread across the dairy industry in Ireland. The distribution of calves slaughtered per herd demonstrate that a small number of herds contributed disproportionately to calf slaughter numbers. Such herds tended to be very large (herd size), more recently established (2016 onwards), and have higher proportions of JE/JEX breed cattle. The outcomes of the present study provide an evidential base for the development of targeted industry-lead interventions with the aim of ending the routine early slaughter of calves.